Advanced multimodal CT/MRI approaches to hyperacute stroke diagnosis, treatment, and monitoring - Liebeskind, David S. (2012)
Multimodal CT/MRI has dramatically changed the approach to ischemic stroke management, as noninvasive CT/MRI images detail brain tissue or parenchyma, angiography or vessel status, and collateral perfusion or blood flow in regions of the brain vulnerable to ischemic injury. Such snapshots of the dynamic process of cerebral ischemia may be used to gauge reversibility and therapeutic opportunities. Treatment of acute stroke may be rapidly tailored to clinical scenarios based on imaging correlation of ischemia, vessel status, and perfusion. Serial or repeated imaging from the initial presentation to later stages of the hospital course may illustrate infarct growth, persisting occlusion, reocclusion, recanalization, reperfusion, and hemorrhagic transformation. From acute stroke to rehabilitation phases and subsequent prevention, multimodal CT/MRI has emerged as a key tool to track the process of stroke and the impact of our therapeutic interventions.